Uji Aktivitas Antioksidan dari Formulasi Spray Gel Kombinasi Fraksi Etil Asetat Rimpang Kunyit dan Kolagen dari Ikan Patin - Denia Pratiwi; Yan Hendrika (JURNAL FARMASI DAN MAKANAN, 2022)
Premature aging is the process of aging skin that it faster than time because there is oxidative damage caused by free radicals. This study aims to determine the antioxidant activity of the cosmeceuticals spray gel combination of turmeric rhizome fraction with catfish skin collagen. Curcumin compounds in turmeric are known to have high antioxidant activity to inhibit free radicals and the addition of collagen is intended to be able to provide intake in improving skin structure due to premature aging. The preparations are made into 8 formulas with various concentration. The preparations formed will be evaluated and tested for their antioxidant activity. The result obtained were the extraction of catfish skin collagen the yield of 12.466% collagen. Examination of the ash content, moisture content, fat and protein contain were obtained respectively 0.0105; 0.0525; 5.98; 85.76%. In the evaluation of spray gel preparations, it was found that the preparations F1-F8 met quality standards on the test of spreadability, adhesion resistance, dry time, pH, spray conditions, except for the viscosity value at F4 and F5. The highest % inhibition value was obtained at F8 (0.5% ethyl acetate fractions of turmeric rhizome and 2% collagen of catfish skin) amounted to 48.82%. In statistical t-test showed sig 0.001, indicates there are significant differences in each formula.